2021
DOI: 10.3390/antibiotics10121542
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Voriconazole Trough Concentration and Optimal Maintenance Voriconazole Dose in Chinese Children

Abstract: Voriconazole is a triazole antifungal agent commonly used for the treatment and prevention of invasive aspergillosis (IA). However, the study of voriconazole's use in children is limited. The present study was performed to explore maintenance dose to optimize voriconazole dosage in children and the factors affecting voriconazole trough concentration. This is a non-interventional retrospective clinical study conducted from 1 January 2016 to 31 December 2020. The study finally included 94 children with 145 voric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Similar to the results of many previous studies (Dolton et al, 2012;Zhao et al, 2021a;Zhao Y. C et al, 2021), the linear regression model found that voriconazole trough concentration is significantly affected by the dose before sampling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to the results of many previous studies (Dolton et al, 2012;Zhao et al, 2021a;Zhao Y. C et al, 2021), the linear regression model found that voriconazole trough concentration is significantly affected by the dose before sampling.…”
Section: Discussionsupporting
confidence: 89%
“…Since the metabolism of voriconazole is regulated by liver enzymes ( Zhong et al, 2018 ), its overexposure may occur in patients with liver damage. Published studies demonstrated that reduced voriconazole elimination is significantly associated with impaired liver function, as indicated by elevated alanine transaminase ( Zhao et al, 2021b ), aspartate transaminase ( Li et al, 2017 ), direct bilirubin ( Zhao Y. C et al, 2021 ) and international normalized ratio levels ( Zhao et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole is a broad-spectrum antifungal agent commonly used for . 8 These different phenotypes can affect the blood concentration of voriconazole in children, [30][31][32] and the adverse events associated with it, with higher concentrations resulting in a relatively higher incidence of adverse reactions. 9,33 The main adverse reactions associated with voriconazole are photosensitivity and abnormal liver function.…”
Section: Voriconazolementioning
confidence: 99%
“…14,15 Of these, CYP2C19 polymorphisms are considered a key determinant of the wide pharmacokinetic (PK) variability of VRC. 16 Low levels of exposure to VRC may result in treatment failure, whereas high levels of exposure may result in adverse neurological effects, hepatotoxicity, and visual impairment. [17][18][19] Therefore, the dosing schedule for VRC should be optimized to maximize the best therapeutic effect and minimize the occurrence of adverse effects.…”
mentioning
confidence: 99%
“…However, VRC has a narrow therapeutic range and complex nonlinear pharmacokinetics; furthermore, multiple factors are known to be associated with the pharmacokinetics of VRC, including age, body weight, liver function, and genetic polymorphisms of the cytochrome P450 (CYP) 2C19 enzyme, all of which complicate the successful therapeutic use of VRC in the pediatric population 14,15 . Of these, CYP2C19 polymorphisms are considered a key determinant of the wide pharmacokinetic (PK) variability of VRC 16 . Low levels of exposure to VRC may result in treatment failure, whereas high levels of exposure may result in adverse neurological effects, hepatotoxicity, and visual impairment 17–19 .…”
mentioning
confidence: 99%